Disease management programs for patients with type 2 diabetes mellitus in Germany: a longitudinal population-based descriptive study - Mehring, Michael (Diabetol Metab Syndr, 2017)
BACKGROUND: The primary aim of the disease management program (DMP) for patients with diabetes mellitus type 2 is to improve the quality of health care and the treatment process. 12 years after its introduction in Germany, there is still no consensus as to whether DMP has been effective in reaching these goals. METHODS: A retrospective longitudinal population-based study between 2004 and 2015 were conducted to evaluate the DMP for type 2 diabetes in Bavaria using routinely collected patient medical records hold from the National Association of Statutory Health Insurance Physicians of Bavaria. RESULTS: During the first 12 years of DMP, the number of participants increased continually to reach 580,222 in 2015. The proportion of participants older than 70 years increased during the observation from 41.6 to 51.1%. The percentage of smokers increased slightly from 9 to 11%. Similarly, the distribution of body mass index remained constant with approximately 50% of patients having a body mass index >30 kg/m(2). Control of HbA1c was without an appreciable change over the course, with between 8.3 and 9.4% of all patients with uncontrolled values higher than 8.5%. Prescription of metformin increased from 40.5% in 2004 to 54.1% in 2015. Among patients receiving insulin, the proportion receiving a combined therapy with metformin increased from 28.4% in 2004 to 50.8% in 2015. In contrast, the percentage with insulin monotherapy decreased from 55.4 to 33.7%. The proportion of patients with a diabetic education increased within the course from 12.8 to 29.3%. CONCLUSION: Data from the German DMP for type 2 diabetes demonstrates an improvement in the quality of care with respect to pharmacotherapy and patient education and therefore to an improved adherence to guidelines. However, no appreciable improvement was observed with regard to smoking status, obesity or HbA1c control.